118k views
5 votes
Topic : Composition of Functions - Worksheet 2 Using f(x) = 5x + 4 and g(x) = x - 3,find: 1. f(g(6)) 2. g(f(-7)) 3. f(f(8)) 4. g(f(x))

1 Answer

4 votes

Answer:


  • f(g(6))=19

  • g(f(-7))=-34

  • f(f(8))=224

  • g(f(x))=5x+1

Explanation:

Considering the functions


f(x) = 5x + 4


g(x) = x - 3

Part 1)

Find


  • f(g(6))

We need to first dertermine
g(6)


g(x) = x - 3

Putting x = 6


g(6) = 6-3=3

Then


f(g(6))=f(3)=5(3)+4=15+4=19

Hence,


f(g(6))=19

Part 2)

Find


  • g(f(-7))

We need to first dertermine
f(-7)


f(x) = 5x + 4

Putting x = -7


f(-7) = 5(-7)+4=-35+4=-31

Then


g(f(-7))=g(-31)=(-31-3)=-34

Hence,


g(f(-7))=-34

Part 3)

Find


  • f(f(8))

We need to first dertermine
f(8)

Putting x = 8


f(8) = 5(8)+4=40+4=44

Then


f(f(8))=f(44)=5(44)+4=220+4=224

Hence,


f(f(8))=224

Part 4)

Find


  • g(f(x))


f(x) = 5x + 4


g(f(x))=g(5x+4)


=(5x+4)-3=5x+1

Hence,


g(f(x))=5x+1

Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.